2023
DOI: 10.1038/s41598-023-35171-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of community-associated methicillin-resistant Staphylococcus aureus ΨUSA300 among Japanese people with HIV, resulted from stepwise mutations in 2010s

Abstract: Although infection with the methicillin-resistant Staphylococcus aureus (MRSA) clone USA300 is extremely rare in Japan, the uniquely evolved clone ΨUSA300 has been reported in Japan. An outbreak of a distinct USA300 clone was recently reported in an HIV/AIDS referral hospital in Tokyo. The present study investigated the evolutionary origin and genetic diversity of USA300-related clones causing regional outbreaks among people living with HIV (PLWHIV) in Tokyo. MRSA isolates collected from PLWHIV in an HIV/AIDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…ΨUSA300 was first identified as a USA300 variant that was misclassified as an isolate harboring SCC mec type I by conventional PCR-based SCC mec typing because of deletion in the binding site of a βc primer ( 15 ). The emergence of ΨUSA300 in Japan has been observed in previous studies ( 16 18 ). The detection rate of PVL genes among MRSA has increased in community settings in many parts of Japan ( 17 20 ).…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…ΨUSA300 was first identified as a USA300 variant that was misclassified as an isolate harboring SCC mec type I by conventional PCR-based SCC mec typing because of deletion in the binding site of a βc primer ( 15 ). The emergence of ΨUSA300 in Japan has been observed in previous studies ( 16 18 ). The detection rate of PVL genes among MRSA has increased in community settings in many parts of Japan ( 17 20 ).…”
Section: Introductionsupporting
confidence: 70%
“…2 ). The USA300 and ΨUSA300 strains isolated in this study were expected to show nearly identical profiles for virulence genes for which the detection process was not conducted, including certain of the genes encoding hemolysin, leukotoxin, staphylococcal enterotoxin, and staphylococcal complement inhibitor, considering the results of previous reports ( 16 , 18 ). Meanwhile, The MICs and resistance gene profiles indicated that USA300 and ΨUSA300 tended to harbor different mobile genetic elements ( Table 2 ).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations